2013
DOI: 10.3892/ijo.2013.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma cells injected into experimental mature teratoma reveal a tropism for embryonic loose mesenchyme

Abstract: Abstract. Embryonic neural tumors are responsible for a disproportionate number of cancer deaths in children. Although dramatic improvements in survival for pediatric malignancy has been achieved in previous years advancements seem to be slowing down. For the development of new enhanced therapy and an increased understanding of the disease, pre-clinical models better capturing the neoplastic niche are essential. Tumors of early childhood present in this respect a particular challenge. Here, we explore how comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Extension of the findings using the hESC-derived microenvironment to other tumors will be needed to demonstrate broad relevance. To date, reproducibility of our previously published results has been demonstrated in two independent publications indicating that the hESC-based model express bona fide human tumor blood vessels and enhance tumor engraftment rate by primary human ovarian CSC-like [37], and that the hESC-based model enable the implantation and growth of childhood neuroectodermal tumors biopsies as it provides an embryonic niche well suited for in vivo studies of neuroblastoma [64]. In addition, mechanistic studies will be required to assess the functional role of the genes exposed in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Extension of the findings using the hESC-derived microenvironment to other tumors will be needed to demonstrate broad relevance. To date, reproducibility of our previously published results has been demonstrated in two independent publications indicating that the hESC-based model express bona fide human tumor blood vessels and enhance tumor engraftment rate by primary human ovarian CSC-like [37], and that the hESC-based model enable the implantation and growth of childhood neuroectodermal tumors biopsies as it provides an embryonic niche well suited for in vivo studies of neuroblastoma [64]. In addition, mechanistic studies will be required to assess the functional role of the genes exposed in this study.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism for such tropism now remains to be tested and we see primarily three main possibilities; (i) the "open" nature of loose mesenchyme may more easily give space to new cells compared to other more dense tissues, (ii) the biophysical properties of the extracellular matrix such as rigidity may provide physical cues, "mechanotransductive signalling," as suggested by Lam et al 21 Alternatively (iii) components of the loose myxoid ground or factors derived from the various cell types present in embryonic loose mesenchyme may supply developmental cues that attract or promote integration. 12 To what extent tropism may be dependent on heterologous versus autologous microenvironments could possibly also be addressed further by using teratomas from induced pluripotent stem cells derived from patients with various tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…This raised to us an intriguing prospect that the embryonic human microenvironment in experimental teratoma could be well matched for studies of childhood tumors of early neuroectodermal origin. In a recent study, we tested this notion by injecting three childhood neuroblastoma (NB) tumor cell lines into mature teratoma, and in parallel as xenografts . Here, we expand the studies on cell lines to using fresh biopsy materials from children with different types of neuroectodermal tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a mature pluripotent stem cell‐induced teratoma (PSCT) has been used as an experimental in vivo microenvironment suitable for in vivo culture of injected cancer cell lines. Neuroblastoma cells revealed a tropism for embryonic loose mesenchyme of teratomas, which resulted in a histology recapitulating NB native presentation in vivo . However, it was shown that rats carrying experimental teratomas were partially or totally protected against the induction (by a single injection of a potent carcinogen) or transplantation of malignant tumors (adenocarcinoma and lymphoma) that killed 100% of the controls, a result which suggested that embryonal tissues are the source of tumor inhibitory factors .…”
Section: Pluripotency/malignancy Teratoma Assaymentioning
confidence: 99%